Richard M. Nixon and European Integration A Reappraisal - Siracusa, Joseph M. (Springer International Publishing, 2018)
This book re-examines the Nixon administration's attitude and approach to the European integration project. The formulation of US policy towards European integration in the Nixon presidential years (1969-1974) was conditioned by the perceived relative decline of the United States, Western European emergence and competition, the feared Communist expansionism, and US national interests. Against that backdrop, the Nixon administration saw the need to re-evaluate its policy on Western Europe and the integration process on this continent. Underpinning this study is the extensive use of newly-released archival materials from the Nixon Presidential Library and Museum, the Library of Congress, and the State Department. Furthermore, the work is based on the public papers in the American Presidency Project and the materials on the topic of European integration and unification in the Archive of European Integration. Finally, the study has extensively used newspaper archives as well as the declassified online documents, memoirs and diaries of former US officials. Mining these sources made it possible to shed new light on the complexity and dynamism of the Nixon administration's policy towards European integration.